2012
DOI: 10.1007/s11605-011-1696-2
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Lesions Identified on Ultrasound. Lessons from the Last 10 Years

Abstract: Despite improvements in imaging, most apparent lesions measuring <5 mm on US are not identified in the surgical specimen. US size >9 mm, age >52 years, US suggestion of invasion at the liver interface, and wall thickening >5 mm, especially in the presence of gallstones, should raise the suspicion of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…According to the management algorithm, which was determined by a review of the literature, management of gallbladder polyps primarily relies on the size of the lesion (Fig 12) (1, 3,17,44,60,[62][63][64][65][66][67][68][69][70][71]. Two large series confirmed that a size larger than 10 mm is the best indicator of malignancy and warrants cholecystectomy (60,61).…”
Section: Management Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the management algorithm, which was determined by a review of the literature, management of gallbladder polyps primarily relies on the size of the lesion (Fig 12) (1, 3,17,44,60,[62][63][64][65][66][67][68][69][70][71]. Two large series confirmed that a size larger than 10 mm is the best indicator of malignancy and warrants cholecystectomy (60,61).…”
Section: Management Algorithmmentioning
confidence: 99%
“…Management of polyps that measure 5 mm or less is also not clearly established. A study found that, among patients with sub-5-mm polyps at preoperative US, no focal lesion was seen in cholecystectomy specimens from more than 80% of patients (66). Another study reported that 24% of sub-5-mm polyps were not seen at follow-up US (63).…”
Section: Management Algorithmmentioning
confidence: 99%
“…The suggested predictive factors of a malignant GB polyp include size (≥10 mm), solitary lesion, age (≥50-60 years), increased size of polyp during follow-up, concurrent gallstones, sessile lesions, and gallbladder wall thickening [1,17,18]. In our study, the significant predictive factors of a Note: ROI = region of interest neoplastic polyp were age (≥57 years), size (≥15 mm), the absence of hyperechoic foci, an irregular margin, a sessile shape, a single polyp, and the presence of adjacent GB wall thickening by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Color Dopple ultrasound distinguishes gallbladder carcinoma from intragallbladder cholestasis according to the blood flow signal. A high-speed blood flow indicates gallbladder carcinoma with the sensitivity of 83.9% and the specificity of 80.5% [10]. CT functions in the diagnosis of gallbladder carcinoma in the distinguishing of it from chronic cholecystitis and gallbladder polyps, the clinical staging and the judgment about resectability.…”
Section: Diagnosismentioning
confidence: 99%